CAN‐mediated Oxidative Coupling‐Reaction of Xanthenes with Enaminones. Issue 1 (10th December 2020) - Zhang, Changyuan; Qiu, Yun; Zhang, Jiantao; Chen, Lulu; Xu, Shuting; Guo, Huosheng; Luo, Jian; Tan, Yao
Abstract: An efficient CAN‐mediated C−C bond formation in the oxidative reactions of xanthenes with enaminones under mild reaction conditions are described. A variety of 9H‐xanthene‐9‐ylidene aldehydes could be synthesized in up to 90% yield via one‐pot manner with good functional group compatibility, which achieved the simultaneous construction of carbon‐carbon double bond and carbon‐oxygen double bond. Abstract : An efficient method for the synthesis 9H‐xanthene‐9‐ylidene aldehydes via CAN‐mediated multi‐step oxidative coupling process of xanthene derivatives has been developed, which realized the construction of carbon‐carbon double bond and carbon‐oxygen double bond.